The Different Insulin-Sensitising and Anti-Inflammatory Effects of Palmitoleic Acid and Oleic Acid in a Prediabetes Model - Denisa Miklankova; Irena Markova; Martina Hüttl; Barbora Stankova; Hana Malinska (Journal of Diabetes Research)
Introduction. Monounsaturated fatty acids (MUFA) are understood to have therapeutic and preventive effects on chronic complications associated with type 2 diabetes mellitus (T2DM); however, there are differences between individual MUFAs. Although the effects of palmitoleic acid (POA) are still debated, POA can regulate glucose homeostasis, lipid metabolism, and cytokine production, thus improving metabolic disorders. In this study, we investigated and compared the metabolic effects of POA and oleic acid (OA) supplementation on glucose and lipid metabolism, insulin sensitivity, and inflammation in a prediabetic model, the hereditary hypertriglyceridemic rat (HHTg). HHTg rats exhibiting genetically determined hypertriglyceridemia, insulin resistance, and impaired glucose tolerance were fed a standard diet. POA and OA were each administered intragastrically at a dose of 100 mg/kg b.wt. for four weeks. Results. Supplementation with both MUFAs significantly elevated insulin and glucagon levels, but only POA decreased nonfasting glucose. POA-treated rats showed elevated circulating NEFA associated with increased lipolysis, lipoprotein lipase gene expression, and fatty acid reesterification in visceral adipose tissue (VAT). The mechanism of improved insulin sensitivity of peripheral tissues (measured as insulin-stimulated lipogenesis and glycogenesis) in POA-treated HHTg rats could contribute increased circulating adiponectin and omentin levels together with elevated FADS1 gene expression in VAT. POA-supplemented rats exhibited markedly decreased proinflammatory cytokine production by VAT, which can alleviate chronic inflammation. OA-supplemented rats exhibited decreased arachidonic acid (AA) profiles and decreased proinflammatory AA-derived metabolites (20-HETE) in membrane phospholipids of peripheral tissues. Slightly increased FADS1 gene expression after OA along with increased adiponectin production by VAT was reflected in slightly ameliorated adipose tissue insulin sensitivity (increased insulin-stimulated lipogenesis). Conclusions. Our results show that POA served as a lipokine, ameliorating insulin sensitivity in peripheral tissue and markedly modulating the metabolic activity of VAT including cytokine secretion. OA had a beneficial effect on lipid metabolism and improved inflammation by modulating AA metabolism.